MODEL AUDIT GOING CONCERN UNTUK KELANGSUNGAN HIDUP PERUSAHAAN - Novi Astuti; Muhammad Fachruddin Arrozi (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of profitability, liquidity and company growth as moderating variables on going concern audit opinions on property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this study was 88 companies in the property and real estate sector listed on the Indonesia Stock Exchange in 2020-2022. The method used was a purposive sampling method so that a sample of 53 companies was obtained and 159 observations were obtained which were determined according to predetermined criteria. The type of data used is secondary data in the form of financial reports sourced from the website www.idx.co.id. Data analysis in this study used logistic regression analysis and the Moderate Regression Analysis (MRA) test which was processed in software in the SPSS version 25 application. The results of this research indicate that profitability, liquidity and company growth simultaneously influence going concern audit opinion. Partially, profitability and liquidity have a significant negative effect on going concern audit opinion, and company growth does not have a significant effect on going concern audit opinion. Company growth cannot moderate the relationship between profitability and liquidity on going concern audit opinion.